Extended Focused Assessment with Sonography for Trauma (eFAST): A Comprehensive Strategy for Trauma Assessment - Vaishali V. Paswan (International Journal of Emergency and Trauma Nursing and Practices, 2024)
Trauma is the principal cause of mortality in individuals under 45 years old, with 80% being due to blunt trauma and most deaths arising from hypovolemic shock. Intraperitoneal bleeding occurs in 12% of these cases, making swift identification of trauma critical. The ideal diagnostic test should be fast, accurate, and non-invasive. The adoption of point-of-care ultrasound has profoundly influenced the management and evaluation of trauma patients. This discussion outlines the use of the Focused Assessment with Sonography in Trauma (FAST) protocol, which evaluates for hemoperitoneum and hemopericardium and has been shown to have sensitivities of 85% to 96% and specificities over 98%. In hypotensive trauma patients, FAST’s sensitivity nears 100%. Performed in under 5 minutes by skilled clinicians, FAST reduces the time to surgical intervention, shortens hospital stays, and lowers the necessity for computed tomography scans and diagnostic peritoneal lavage. Currently, over 96% of level 1 trauma centers employ FAST in their protocols, aligned with the Advanced Trauma Life Support (ATLS) guidelines. Additionally, many centers have integrated the Extended FAST (eFAST) protocol, which additionally checks each hemithorax for hemothoraces and pneumothoraces, into their procedures.
Keywords: Focused Assessment with Sonography in Trauma (FAST); extended Focused Assessment with Sonography in Trauma (eFAST); hemoperitoneum; hemothorax; left upper quadrant; non-invasive; right upper quadrant; trauma